Binary Option sebagai Praktik Investasi dalam Perspektif Maqashid Al-Syariah - Kholil, Mohammad; Wardi, Moch. Cholid (Jurnal Ilmiah Ekonomi Islam, 2025)
In Indonesian society today, binary options have emerged as a new trend that has attracted public attention., as the platform is seen as a quick means of gaining profits. However, the lack of public understanding of the concept and mechanism of such trading is believed to lead to more gambling. This is evidenced by the binary option transaction system which is more similar to a zero-sum game, as well as the results of profits obtained solely based on predictions of the rise and fall of an asset, without having to own the asset being traded. This study aims to analyze the status of binary options as a legitimate investment or even as prohibited gambling from the perspective of maqashid syariah. The method in this study uses a qualitative approach derived from secondary data. The data collection technique used is library research with data analysis techniques are content analysis and induction. The findings of this study are that binary option trading does not meet the characteristics of investment in Islam and contains elements of maysir (speculation) and gharar (uncertainty) which are explicitly prohibited in Islam. So this activity can be categorized as more similar to gambling. From a maqashid perspective, it can be categorized as practices that are contrary to the principle of hifdz al-mal (protection of wealth) which can threaten the benefit and blessing of wealth. Therefore, this study recommends sharia-based education to help people choose the type of investment that is legal, and in accordance with Islamic principles.